(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
The purpose of this paper is to investigate the influence of calendering process on polypropylene nonwoven structure and thermal resistance. The study was focused on the influence of mass per unit area, thickness, density, porosity, characteristic opening size and additional thermal bonding by calendering. Thermal resistance of polypropylene nonwoven fabric manufactured using the mechanical carding process and bonding using the needling process, where a part of the samples was additionally bonded by the thermal calendering process, were investigated. The nonwoven fabrics were tested for thermal resistance on the guarded hot plate. Statistical analyses were performed to examine the significance between the observed parameters. Correlation matrix analyses were used to reveal relationship behaviour among the variables. A change in structure of the calendered samples caused a considerably lower thermal resistance i.e. better thermal conductivity. A change of the average value of thermal resistance after calendering related to non-calendered fabric mass between 150 and 500 g/m² ranged from 53.9 to 41.0%. With increasing nonwoven fabric mass, the difference between thermal resistances of needled and needled as well as additionally bonded by calendering the nonwoven fabric was reduced.